Palaeoceanographic and palaeoclimatic inferences from Late Cretaceous planktonic foraminiferal assemblages from the Exmouth Plateau (ODP Sites 762 and 763, eastern Indian Ocean) - M.R. Petrizzo (Marine Micropaleontology, 2002)
The evolution of planktonic foraminifera during the Late Cretaceous is marked in the Santonian by the disappearance of complex morphotypes (the marginotruncanids), and the contemporary increasing importance and diversification of another group of complex taxa, the globotruncanids. Upper Turonian to lower Campanian planktonic foraminiferal assemblages from Holes 762C and 763B (Ocean Drilling Program, Leg 122, Exmouth Plateau, 47°S palaeolatitude) were studied in detail to evaluate the compositional variations at the genus and species level based on the assumption that, in the Cretaceous oceans as in the modern, any faunal change was associated with changes in the characteristics and the degree of stability of the oceanic surface waters. Three major groups were recognised based on gross morphology, and following the assumption that Cretaceous planktonic foraminifera, although extinct, had life-history strategies comparable to those of modern planktonics. 1 - r-selected opportunists; 2 - k-selected specialists; 3 - r/k intermediate morphotypes which include all genera that display a range of trophic strategies in-between opportunist and specialist taxa. Although planktonic foraminiferal assemblages are characterised by a progressive appearance of complex taxa, this trend is discontinuous. Variation in number of species and specimens within genera has allowed recognition of five discrete intervals each of them reflecting different oceanic conditions based on fluctuations in diversity and abundance of the major morphotypes. Planktonic forms show cyclical fluctuations in diversity and abundance of cold (r-strategists) and warm taxa (k-strategists), perhaps representing alternating phases of unstable conditions (suggesting a weakly stratified upper water column in a mesotrophic environment), and well-stratified surface and near-surface waters (indicating a more oligotrophic environment). Interval 1, middle Turonian to early Coniacian in age, is dominated by the r/k intermediate morphotypes which alternate with ...